Collins: maths dictionary - Gardner, Kay (HarperCollins London, 2002)
This Key Stage 2 maths dictionary is packed with the vocabulary definitions recommended for years 3 to 6 by the National Numeracy Framework. It contains over 375 entries using the recommended yearly vocabulary with headwords, guidewords and a thumb index.